2022
DOI: 10.15586/qas.v14isp1.1114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on thin-layer drying kinetics of sprouted wheat in a tray dryer

Abstract: The thin-layer drying behavior of sprouted wheat (cv. PBW 550) was experimented at different drying periods, such as 24 h, 36 h and 48 h. The samples were dried in a tray dryer at 50–80οC at an interval of 10°C. The moisture ratio was fitted to the six thin-layer drying models, and the performance of the models was assessed by statistical parameters. The Wang and Singh model has accurately predicted the drying behavior of sprouted wheat for all sprouting periods and drying temperatures. In addition, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Also, the D eff value for tray and vacuum dryers was reported between 3.98 × 10 −11 and 7.35 × 10 −11 m 2 s −1 , and 4.50 × 10 −11 and 7.892 × 10 −11 m 2 s −1 , respectively. Manikantan et al (2022) used a tray dryer (at 50–80°C for 24–48 h) for drying sprouted wheat grains. Their results showed that the D eff values of sprouted wheat grains (at a 48‐h drying period) increased from 1.9 × 10 −9 to 2.6 × 10 −9 m 2 s −1 with an increase in dryer temperature from 50 to 80°C.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, the D eff value for tray and vacuum dryers was reported between 3.98 × 10 −11 and 7.35 × 10 −11 m 2 s −1 , and 4.50 × 10 −11 and 7.892 × 10 −11 m 2 s −1 , respectively. Manikantan et al (2022) used a tray dryer (at 50–80°C for 24–48 h) for drying sprouted wheat grains. Their results showed that the D eff values of sprouted wheat grains (at a 48‐h drying period) increased from 1.9 × 10 −9 to 2.6 × 10 −9 m 2 s −1 with an increase in dryer temperature from 50 to 80°C.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the Sarjerao et al (2022) study indicated that modified Henderson and Pabis was the appropriately fitted equation for sprouted mung bean dehydration in trays and vacuum dryers. In another study, Manikantan et al (2022) used the Wang and Singh model to predict the dehydration kinetics of germinated wheat grains in a tray dryer. The authors reported that this equation can accurately predict the dehydration kinetics of wheat sprouts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic susceptibility factors play a significant role in the development of celiac disease, an autoimmune condition that may cause significant intestine damage. In the general community, celiac disease affects 0.5% to 1% of people (Giménez‐Bastida et al, 2015 ; Manikantan et al, 2022 ; Rafiq et al, 2021 ). Contrarily, gluten sensitivity and/or other wheat proteins is caused by IgE antibodies that identify epitopes from certain proteins, known as allergens, setting off a chain of events that results in allergic inflammation.…”
Section: Introductionmentioning
confidence: 99%